Chitosan as an Immunomodulating Adjuvant on T-Cells and Antigen-Presenting Cells in Herpes Simplex Virus Type 1 Infection - Bunsoon Choi; Do-Hyun Jo; A. K. M. Mostafa Anower; S. M. Shamsul Islam; Seonghyang Sohn (Mediators of Inflammation)
Herpes disease caused by herpes simplex virus type 1 (HSV-1) is an intractable condition. It is a major concern in public health. Our purpose of this study was to verify the function of chitosan as an adjuvant for immune regulation specifically under herpes simplex virus type 1 (HSV-1) infection. Ahead of HSV infection, chitosan, heat inactivated green fluorescent protein expressing HSV (G-HSV), and a combination of chitosan and G-HSV were used to pretreat ICR mice followed by HSV-1 infection. Using flow cytometric analysis, the frequencies of T-cells, monocytes, dendritic cells (DCs), and natural killer (NK) cells were analyzed by surface expression of CD4+, CD8+, CD14+, CD11c+, NK1.1+, and DX5+ cells. In HSV infected mice, chitosan treatment significantly increased the frequencies of CD4+ T-cells (33.6±5.78%) compared to those in the control group (24.02±12.47%, p=0.05). The frequencies of DC and NK cells were also significantly different between chitosan treated mice and control mice. In addition, anti-HSV IgG antibody was downregulated in chitosan treated mice. These results suggest that chitosan is a potential modulator or immune stimulator as an adjuvant in HSV-1 infected mice.